Pelvic inlet area is associated with birth mode. (1st November 2022) - Starrach, Teresa; Schmidhuber, Lisa; Elger, Luisa; Franz, Marie; Buechel, Johanna; Hübener, Christoph; Kolben, Thomas; Koliogiannis, Vanessa; Mahner, Sven; Hasbargen, Uwe; Fischer, Barbara
Abstract: Introduction: To determine whether a pelvis is wide enough for spontaneous delivery has long been the subject of obstetric research. A number of variables have been proposed as predictors, all with limited accuracy. In this study, we use a novel three‐dimensional (3D) method to measure the female pelvis and assess which pelvic features influence birth mode. We compare the 3D pelvic morphology of women who delivered vaginally, women who had cesarean sections, and nulliparous women. The aim of this study is to identify differences in pelvic morphology between these groups. Material and methods: This observational study included women aged 50 years and older who underwent a CT scan of the pelvis for any medical indication. We recorded biometric data including height, weight, and age, and obtained the obstetric history. The bony pelvis was extracted from the CT scans and reconstructed in three dimensions. By placing 274 landmarks on each surface model, the pelvises were measured in detail. The pelvic inlet was measured using 32 landmarks. The trial was registered at the German Clinical Trials Register DRKS (DRKS00017690). Results: For this study, 206 women were screened. Exclusion criteria were foreign material in the bony pelvis, unknown birth mode, and exclusively preterm births. Women who had both a vaginal birth and a cesarean section were excluded from the group comparison. We compared the pelvises of 177 women between three groups divided by obstetric history: vaginal births only ( n = 118), cesarean sections only ( n = 21), and nulliparous women ( n = 38). The inlet area was significantly smaller in the cesarean section group (mean = 126.3 cm 2 ) compared with the vaginal birth group (mean = 134.9 cm 2, p = 0.002). The nulliparous women were used as a control group: there was no statistically significant difference in pelvic inlet area between the nulliparous and vaginal birth groups. Conclusions: By placing 274 landmarks on a pelvis reconstructed in 3D, a very precise measurement of the morphology of the pelvis is possible. We identified a significant difference in pelvic inlet area between women with vaginal delivery and those with cesarean section. A unique feature of this study is the method of measurement of the bony pelvis that goes beyond linear distance measurements as used in previous pelvimetric studies. Abstract : Women who delivered by cesarean section have a significantly smaller pelvic inlet area. With this 3D measurement method, not only distances at the pelvic inlet but the complete three‐dimensional pelvic morphology can be recorded.